Human-Robot Interaction Based GUI - Rahmat Fauzi Siregar; Ramadoni Syahputra; Muhamad Yusvin Mustar (Universitas Muhammadiyah Yogyakarta, 2017)
Nowadays, technological developments interactions in general, couldn't be separated from the rapid development of computer technology and human interaction. So that, supporting the user to be able to develop various models of interactions, especially the interactions between humans and robots. This study proposes a model of design and manufacture of human and robot interaction, in the form of a visual display on a computer controlling the robot motion. Object interaction in this study is using 4WD Smart Car Robot. Some of the tools used to build a robot control system at the time of interaction, including Netbeans IDE, based on JAVA and Arduino. The control algorithm is applied to build an optimal control system to model an interaction between humans and robots. Model of human interaction and robot is fully carried by the user in control of robot motion. The proposed interaction model can be implemented in real terms, in designing and making a model of human interaction and robot.